Freshwater fish from Mzinyashana Shelter 1, Thukela Basin, KwaZulu-Natal - Hall, S. (Southern African Humanities, 2021)
Analysis of a small sample of fresh water fish from Mzinyashana Shelter 1 suggests that between 4000 b.p. and 2000 b.p. fish did not contribute much to the hunter-gatherer diet. Thereafter, however, a perceptible increase in abundance peaks at about 970 b.p. A corresponding increase in species diversity suggests that intensification was coupled with the addition of a mass capture technology, and that these trends can be correlated with the appearance of mixed farmers in the Thukela Basin. To cite this paper: Hall, S. 1997. Freshwater fish from Mzinyashana Shelter 1, Thukela Basin, KwaZulu-Natal. Natal Museum Journal of Humanities 9: 47-55.